PENGARUH SUPLEMENTASI DL-METIONIN DAN L-LISIN HCL PADA PAKAN STANDAR KAFETARIA TERHADAP BERAT BADAN, ORGAN DALAM DAN ORGAN REPRODUKSI AYAM KAMPUNG FASE PULLET - Lisnahan, Charles V.; Wihandoyo, Wihandoyo; Zuprizal, Zuprizal; Harimurti, Sri (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The aim of this study was to determine the effect of the supplementation of dl-methionine and l-lysine HCl to diet based on cafeteria standards of native chickens on body weight, internal organs and reproductive organs of native chicken at pullet phase. A total of 128 fourteen weeks-old native chickens were used in this study. The native chickens were divided into 4 treatments with 4 replications. The dietary treatments were: T0 (ration based on cafeteria standard), T1 (ration based on protein standard of NRC), T2 (cafeteria ration+0.09% DL-Methionine+0.22% L-Lysine HCl), T3 (cafeteria ration+0.19% dl-methionine+0.42% l-lysine HCl). The data collected were body weight, liver and bile, pancreas, gizzard, testicular and ovary weight  of native chickens aged 20 weeks. The result of this study for T0, T1, T2 and T3 showed that body weight of chickens were 1418.60; 1431.59; 1503.88 and 1556.41 g/bird, liver and bile weights were 22.44; 21.79; 24.49 dan 25.93 g/bird, pancreas weights were 2.33; 2.28; 2.50 and 2.70 g/bird, gizzard weight were 25.31; 23.91; 25.38 and 26.86 g/bird, testicular weight were 3.66; 3.86; 9.55 and 9.46 g/bird, testicular volume were 3.81; 3.38; 9.13 and 9.16 and ovary weight were 1.12; 1.32; 3.14 and 4.61 g/bird, respectively. The results showed that supplementation of DL-Methionine and L-Lysine HCl gave significantly effect (P<0.05) upon body weight, liver and bile weight, pancreas weight, testicular weight and volume and ovary weight, but it did not effected to gizzard weight. It can be concluded that supplementation of 0.27% dl-methionine and 0.79% l-lysine HCl increase body weight, internal organs weight and reproductive organs weight of native chickens.  Keywords: Cafeteria, DL-Methionine, L-Lysine HCl, Native Chicken, Supplementation